ANALISIS KUALITAS AUDITOR DAN MANAJEMEN LABA TERHADAP OPINI AUDIT - Hendro Sasongko; Agung Fajar Ilmiyono; Heni Nelawati (JIAFE (Jurnal Ilmiah Akuntansi Fakultas Ekonomi), 2019)
In this globalization era, there are some cases about company's finance data manipulation especially from major bank listed in the stock exchange that finally went bankrupt and cause public accountant got many critics. Audit opinions that given by auditor denote some important information for financial statement's user. Thus the purposes of this research are examining and analyzing the effect of auditor's quality and earning management to audit opinion on company's sub-sector bank and finance sector listed in Indonesia Stock Exchange period 2015-2017. The sample used in this study amounted to 30 companies using logistic regression analysis techniques. The results showed that auditor quality was not significantly effect for audit opinion while earnings management had a significant effect on audit opinion.